Sunday

April 20, 2014

April 20, 2014

Posted by **Stanley** on Wednesday, March 14, 2012 at 7:29am.

- math -
**Reiny**, Wednesday, March 14, 2012 at 8:06amsquare both sides

t^2 = v/(1/f + 1/g)

t^2 = v/( (f+g)/(fg) )

t^2 = vfg/(f+g)

ft^2 + gt^2 = vfg

ft^2 - vfg = -gt^2

f(t^2 - vg) = -gt^2

f = -gt^2/(t^2 - vg) or gt^2/(vg - t^2)

**Related Questions**

Math/Prob - Claire takes a five-question true-false test. She hasn't studied, so...

math - How would you establish this identity: (1+sec(beta))/(sec(beta))=(sin^2(...

math - flip a coin 3 times a) what are the odds in favor of getting exactly 2 ...

Trigonometry - I need to prove that the following is true. Thanks. csc^2(A/2)=...

Math Integration - i keep getting stuck and i think im missing something ...

Math - Calculus - The identity below is significant because it relates 3 ...

Calc - evaluate the indefinite integral: x^13(cos(x^7))dx I've tried using ...

Math - How would you simplify and prove (csc x - cot x)^2 = (1-cos x)/(1+cos x...

Math - How would you simplify and prove (csc x - cot x) = (1-cos x)/(1+cos x)? I...

science - 4. Bacillus thuringiensis (Bt) is a bacterium that contains a gene ...